A comparative study on phosphotransferase activity of acid phosphatases from Raoultella planticola and Enterobacter aerogenes on nucleosides, sugars, and related compounds - Médici, Rosario (2014)
Natural and modified nucleoside-5′-monophosphates and their precursors are valuable compounds widely used in biochemical studies. Bacterial nonspecific acid phosphatases (NSAPs) are a group of enzymes involved in the hydrolysis of phosphoester bonds, and some of them exhibit phosphotransferase activity. NSAP containing Enterobacter aerogenes and Raoultella planticola whole cells were evaluated in the phosphorylation of a wide range of nucleosides and nucleoside precursors using pyrophosphate as phosphate donor. To increase the productivity of the process, we developed two genetically modified strains of Escherichia coli which overexpressed NSAPs of E. aerogenes and R. planticola. These new recombinant microorganisms (E. coli BL21 pET22b-phoEa and E. coli BL21 pET22b-phoRp) showed higher activity than the corresponding wild-type strains. Reductions in the reaction times from 21 h to 60 min, from 4 h to 15 min, and from 24 h to 40 min in cases of dihydroxyacetone, inosine, and fludarabine, respectively, were obtained.